Factors of the income inequality in the Baltics: Income, policy, demography - Jekaterina Navicke (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This paper aims to disentangle the driving factors behind the changes in income inequality in the Baltics since the EU accession, distinguishing between primary income effect, discrete changes in tax-benefit policies and demographic effect. Evaluation of the three effects was based on counterfactual scenarios, which were constructed using taxbenefit microsimulation and re-weighting techniques. Decomposition of the total change in inequality showed that income and policy effects are dominant in the Baltics. Policy effects were inequality reducing before the crisis and for the period after the EU accession as a whole. Income effects were inequality increasing before the crisis and as a whole. Despite rapid demographic changes in the Baltics, the demographic effects on income inequality were marginal and in general inequality-increasing.
Keywords: D31; H23; I38; J10; 330; inequality; income; demographic change; policy reform; Baltics